(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to measure the level of cognitive insight among kindergarten students and to identify the differences in their possession of cognitive insight according to the variable of the school stage, for the first, second, third and fourth stages. The sample of the study consisted of a group of (400) female students in the Kindergarten Department, distributed over (4) educational stages in the Kindergarten Department of Al-Mustansiriya University, and by using appropriate statistical methods, the results showed that the sample members possessed a level of cognitive insight, and there were no differences. Statistically significant in their possession of cognitive insight according to the academic stage, in the light of the results of the study, the two researchers put forward a number of recommendations and proposals.